Recycled concrete wall material and preparation method thereof

By optimizing the formulation and preparation process of recycled concrete, the problems of performance stability and imperfect preparation process in its application are solved, and the effect of efficient use of construction waste, reducing energy consumption and improving material performance is achieved.

CN119390404AInactive Publication Date: 2025-02-07JIANGSU HUASHENG NEW BUILDING TECH CO LTD
View PDF 0 Cites 10 Cited by

Patent Information

Application Number
CN202411357445.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing recycled concrete faces performance stability problems and imperfect preparation technology in applications, resulting in limited application in building structures such as walls.

Method used

Using a recycled concrete wall material containing recycled coarse aggregate, recycled fine aggregate, cement, fly ash, water reducer, reinforced fibers and modified compositions, by optimizing raw material pretreatment, improving stirring and curing technology, Improve material uniformity and performance.

Benefits of technology

It realizes efficient utilization of recycled concrete, reduces natural aggregate mining and energy consumption, improves the strength, durability and waterproof performance of materials, and meets the diversified needs of different building structures for wall materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390404A_ABST
    Figure CN119390404A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete wall materials, and discloses a recycled concrete wall material and a preparation method thereof, the recycled concrete wall material comprises the following components by weight: 300-500 parts of recycled coarse aggregate, 200-400 parts of recycled fine aggregate, 150-300 parts of cement, 30-80 parts of fly ash, 3-8 parts of a water reducer, 5-15 parts of reinforced fiber, and 20-30 parts of a modified composition. Comprising the following steps: S1, raw material pretreatment, S2, mixing and stirring, S3, molding and curing, and S4, quality detection. The building waste is efficiently utilized, exploitation of natural aggregate is reduced, energy consumption and carbon emission in the production process are reduced, the landfill amount of the building waste and land occupation are reduced, the material strength and durability are good, the waterproof performance is improved, and the crack resistance and seismic resistance of the wall are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete wall materials, in particular to a recycled concrete wall material and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization and the booming construction industry, the demand for building materials is growing. However, the extensive use of traditional building materials not only consumes a large amount of natural resources, such as natural sand, gravel, cement, etc., but also causes serious damage to the environment, such as ecological damage caused by mining and increased carbon emissions. At the same time, the large amount of construction waste has also brought tremendous pressure to the urban environment and waste disposal. According to statistics, the world generates tens of billions of tons of construction waste each year, most of which is landfilled or discarded at will, which not only occupies land resources, but also may cause environmental pollution and safety hazards. Therefore, finding sustainable alternatives to building materials and innovative methods for preparing building materials has become an urgent need for the construction industry to achieve sustainable development.

[0003] Recycled concrete, as a new type of building material made from recycled aggregates from construction waste, has significant environmental and economic benefits. By recycling, crushing, screening and processing discarded concrete, bricks and tiles and other building materials, recycled aggregates can be obtained to replace part of natural aggregates in the preparation of concrete. This can not only reduce the mining of natural aggregates and reduce resource consumption, but also achieve the recycling of construction waste and reduce waste emissions. However, recycled concrete still faces some challenges in its application.

[0004] Performance stability issues: Compared with natural aggregates, the physical and chemical properties of recycled aggregates are somewhat different. The surface of recycled aggregates is usually attached with old cement mortar, resulting in high water absorption, low strength, and may contain some impurities and harmful substances. These factors will affect the workability, strength, durability and other properties of recycled concrete, and its application in building structures such as walls is subject to certain restrictions.

[0005] Imperfect preparation process: Most of the existing recycled concrete preparation methods are simple improvements based on the traditional concrete preparation process, lacking special optimization for the characteristics of recycled aggregates. For example, it is difficult to achieve sufficient and uniform mixing of recycled aggregates and other raw materials during the mixing process, resulting in uneven internal structure of concrete; during the curing process, due to the high water absorption rate of recycled aggregates, it is easy to cause uneven distribution of moisture inside the concrete, affecting the hydration reaction of cement and the strength development of the material. In addition, the existing preparation process has limited means to improve the performance of recycled concrete, and it is difficult to meet the diverse needs of different building structures for wall materials.

[0006] In recent years, with the continuous advancement of materials science and construction technology, some new materials and technologies have gradually emerged, providing new opportunities for the innovation and development of recycled concrete wall materials.

[0007] Application of nanomaterials: Nanomaterials such as nanosilica, graphene quantum dots, and carbon nanotubes have unique physical and chemical properties, such as high specific surface area, excellent mechanical properties, and electrical conductivity. Applying these nanomaterials to recycled concrete can improve the microstructure of concrete and enhance its strength, durability, and other special properties. For example, nanosilica can fill the pores inside concrete, reducing water penetration and the intrusion of harmful substances; graphene quantum dots and carbon nanotubes can enhance the electrical conductivity of concrete, making it possible to realize smart buildings.

[0008] Advanced mixing and curing technologies: Ultrasonic-assisted mixing technology can utilize the special effects of ultrasound to promote the mixing and chemical reaction of raw materials, thereby improving the uniformity and performance of concrete; vacuum dehydration technology can accelerate the forming and early strength development of concrete, thereby improving production efficiency; accelerated curing methods such as steam curing and hot water curing can shorten the curing time, improve the early strength of the material, and meet the needs of rapid construction.

[0009] Fusion of multifunctional materials: Redispersible latex powder can improve the flexibility and bonding properties of concrete, and enhance the crack resistance and waterproofness of walls; the addition of waterproofing agents and flame retardants can give wall materials specific waterproof and fireproof functions to meet the requirements of different building environments; the application of sound-absorbing materials can enhance the sound insulation effect of walls and improve the quality of indoor environments.

[0010] In summary, in order to give full play to the advantages of recycled concrete, solve the problems existing in its application, and combine the development of innovative materials and technologies, it is of great practical significance and application value to develop a high-performance recycled concrete wall material and its advanced preparation method. Summary of the invention

[0011] 1. Technical issues to be solved

[0012] In view of the deficiencies in the prior art, the present invention provides a recycled concrete wall material and a preparation method thereof.

[0013] (II) Technical solution

[0014] A recycled concrete wall material comprising the following components by weight:

[0015] Recycled coarse aggregate: 300 to 500 parts, the particle size of recycled coarse aggregate is 5 mm to 30 mm, and its source is the product of construction waste after crushing, screening and washing, with a water absorption rate not exceeding 8% and a crushing index not exceeding 25%;

[0016] Recycled fine aggregate: 200 to 400 parts. The particle size of recycled fine aggregate is 0.15 mm to 4.75 mm. It is made from waste concrete and bricks and tiles in construction waste through a specific process, and the fineness modulus is between 2.3 and 3.0;

[0017] Cement: 150 to 300 parts, using ordinary Portland cement, with a strength grade of no less than 42.5, and its quality should comply with relevant national standards;

[0018] Fly ash: 30 to 80 parts. The fineness of the fly ash shall not exceed 20% after passing through a 45μm square mesh sieve, the loss on ignition shall not exceed 8%, and its activity index shall not be less than 70%;

[0019] Water reducing agent: 3 to 8 parts, use high-efficiency polycarboxylate water reducing agent, the water reducing rate should not be less than 25%;

[0020] Reinforcement fiber: 5 to 15 parts, the reinforcement fiber is a mixed fiber composed of polypropylene fiber and basalt fiber in a mass ratio of 1:2, and the fiber length is 6 mm to 12 mm;

[0021] Modified composition: 20 to 30 parts, the modified composition consists of nano-silicon dioxide, silica fume, redispersible latex powder, graphene quantum dots and carbon nanotubes in a mass ratio of 3:4:2:0.5:0.5; nano-silicon dioxide can fill the pores inside the concrete and improve the density and strength of the material; silica fume has volcanic ash activity and can react with cement hydration products to enhance the durability of the material; redispersible latex powder can improve the flexibility and bonding properties of concrete; graphene quantum dots have excellent mechanical properties and conductive properties, which can improve the strength and antistatic properties of wall materials; carbon nanotubes have extremely high strength and toughness, which can enhance the mechanical properties and crack resistance of the material.

[0022] Preferably, the formula further contains 5 to 12 parts by weight of slag powder, and the specific surface area of ​​the slag powder is not less than 400 m 2 / kg, and its activity index is not less than 95%;

[0023] According to different wall usage requirements and environmental conditions, the mass ratio of each component in the recycled coarse aggregate, recycled fine aggregate, cement, fly ash, reinforcing fiber and modified composition can be appropriately adjusted; for example, in walls with higher requirements for thermal insulation performance, the proportion of graphene quantum dots and carbon nanotubes can be appropriately increased to improve the thermal resistance of the material.

[0024] Preferably, the method comprises the following steps:

[0025] S1, raw material pretreatment steps:

[0026] The recycled coarse aggregate and recycled fine aggregate are cleaned and dried separately to remove impurities and moisture. The cleaning process adopts a multi-stage flushing process to ensure that the attachments and dust on the surface of the aggregate are effectively removed, and the moisture content of the dried aggregate does not exceed 2%.

[0027] Cement, fly ash and slag powder are screened with a mesh size of 0.3 mm to remove lumps and large particles of impurities to ensure the fineness and uniformity of the raw materials;

[0028] The reinforcing fibers are dispersed by combining mechanical stirring with the addition of dispersants to ensure that the fibers are evenly distributed in the material to avoid agglomeration. The amount of dispersants used is 1% to 2% of the fiber mass.

[0029] Premixing a modified composition consisting of nano-silicon dioxide, silica fume, redispersible latex powder, graphene quantum dots and carbon nanotubes to ensure that the components are evenly mixed to form a modified composition for standby use;

[0030] S2, mixing and stirring step:

[0031] Add the pre-treated recycled coarse aggregate, recycled fine aggregate, cement, fly ash and slag powder into a forced mixer and stir for 1 to 2 minutes to preliminarily mix the raw materials;

[0032] Then add water and water reducing agent. The amount of water is adjusted according to the workability requirements of the material and the performance of the water reducing agent. Generally, the water-to-binder ratio is controlled between 0.3 and 0.5. Continue stirring for 2 to 3 minutes to fully mix the materials.

[0033] During the mixing process, reinforcing fibers and modified compositions are added in stages to ensure that the fibers and modified compositions can be evenly dispersed in the concrete while avoiding damage to the fibers;

[0034] S3, molding and curing steps:

[0035] Pour the stirred concrete mixture into a pre-prepared mold and use vibration molding or extrusion molding to compact the material. The vibration frequency is 30Hz to 50Hz and the vibration time is 10 seconds to 30 seconds to ensure that there are no pores and gaps inside the material.

[0036] After forming, the wall material is kept moisturized at room temperature for no less than 7 days. During the curing process, plastic film is covered or curing agent is sprayed to maintain the humidity of the material surface, promote the hydration reaction of cement and the development of material strength.

[0037] S4, quality inspection and packaging steps:

[0038] Carry out quality inspection on the wall materials after curing, including compressive strength, tensile strength, water absorption, thermal conductivity, to ensure that the performance of the materials meets the design requirements and relevant standards, among which the compressive strength shall not be less than 20MPa, the tensile strength shall not be less than 2MPa, the water absorption shall not exceed 8%, and the thermal conductivity shall be set according to different insulation requirements;

[0039] Qualified wall materials are packaged and stored. The packaging materials are moisture-proof and shock-proof materials, such as plastic film and wooden pallets. The packaging specifications are designed according to the product size and transportation requirements. The product name, specifications, production date and other information should be marked on the packaging so that users can understand the product's performance and quality.

[0040] Preferably, in step S1, the recycled aggregate may be subjected to surface modification treatment, such as spraying or immersing the aggregate surface with a silane coupling agent or a polymer emulsion, to improve the bonding performance between the aggregate and the cement matrix, and the water absorption rate of the treated aggregate surface is reduced, and the bonding strength with the cement is improved;

[0041] In step S2, an appropriate amount of air entraining agent or defoaming agent may be added as needed to adjust the air content and workability of the concrete. The amount of the air entraining agent is 0.01% to 0.05% of the mass of the cement, and the amount of the defoaming agent is appropriately adjusted according to the bubble content in the concrete;

[0042] In step S3, accelerated curing methods such as steam curing or hot water curing can be used to shorten the curing time and improve production efficiency. The temperature of steam curing is 60°C to 90°C, and the curing time is 8 hours to 24 hours; the water temperature of hot water curing is 40°C to 60°C, and the curing time is not less than 48 hours;

[0043] In step S4, a strict quality traceability system is established to record and archive the production process and quality inspection data of each batch of products so that quality problems can be traced and solved in time. At the same time, according to the characteristics of the products and transportation requirements, the packaging design is optimized to improve the protective performance and transportation efficiency of the packaging.

[0044] Preferably, a special waterproofing agent is added to the formula. The waterproofing agent is a mixed waterproofing agent composed of an organic silicon waterproofing agent and a polymer cement-based waterproofing coating in a mass ratio of 1:2, and the added amount is 2% to 5% of the total mass of the material. It can form a dense waterproof film inside the wall material, effectively prevent water penetration, and improve the waterproof performance of the wall;

[0045] According to the fire protection requirements of the wall, an appropriate amount of flame retardant can be added. A composite flame retardant composed of aluminum hydroxide and magnesium hydroxide in a mass ratio of 1:1 is used, and the added amount is 5% to 10% of the total mass of the material. The flame retardant can play a role in heat insulation and flame retardancy when a fire occurs, thereby improving the fire safety of the wall.

[0046] Preferably, in step S2, ultrasonic assisted stirring technology can be used to utilize the cavitation effect and mechanical effect of ultrasound to promote mixing and chemical reaction between the components and improve the uniformity and performance of the material. The frequency of ultrasound is 20kHz to 40kHz, the power is 500W to 1000W, and the stirring time is 5 minutes to 10 minutes.

[0047] In step S3, vacuum dehydration technology can be used to place the formed wall material in a vacuum environment, accelerate the discharge of moisture by reducing the air pressure, and improve the density and early strength of the material. The vacuum degree is controlled at -0.06MPa to -0.08MPa, and the dehydration time is 10 minutes to 20 minutes.

[0048] Preferably, the sound insulation performance of the wall material is optimized, and sound-absorbing materials such as perlite, rock wool, etc. are added to the formula. The amount of sound-absorbing materials added is 10% to 20% of the total mass of the material, and is adjusted according to different sound insulation requirements. The sound-absorbing materials can absorb sound wave energy, reduce the sound transmission coefficient of the wall, and improve the sound insulation effect of the wall;

[0049] According to the decoration requirements of the wall, a layer of color coating or decorative material can be added to the surface of the material. The color coating can adopt environmentally friendly water-based paint with good adhesion and durability. The decorative materials can be selected from tiles, stones, etc., which are firmly combined with the wall materials through special adhesives to improve the aesthetics of the wall.

[0050] Preferably, in step S4, in addition to conventional physical property testing, a durability test may also be performed, the durability test including a freeze-thaw cycle test, a chloride ion penetration test, etc., to evaluate the performance stability of the wall material during long-term use, and formulate corresponding durability indicators and test methods according to different use environments and requirements;

[0051] During the packaging and storage process, intelligent packaging technology can be used. For example, sensors can be embedded in packaging materials to monitor parameters such as humidity and temperature of wall materials to ensure the stability of material quality during storage and transportation. At the same time, the Internet of Things technology can be used to achieve full tracking and management of packaging and products.

[0052] (III) Beneficial technical effects

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] Efficiently utilize construction waste, reduce natural aggregate mining, and reduce ecological damage caused by mining. Every ton of recycled aggregate used can reduce about 0.8 tons of natural aggregate mining.

[0055] Reduce energy consumption and carbon emissions during the production process, which can reduce carbon emissions by about 30% to 40% compared to traditional wall material production.

[0056] Reduce the amount of construction waste landfill and land occupation, and effectively alleviate the pressure of waste disposal.

[0057] The innovative modified composition enhances the strength and durability of the material, with a compressive strength of no less than 20MPa and a tensile strength of no less than 2MPa. The volcanic ash activity of the silica ash also improves durability.

[0058] Special waterproofing agents form a waterproof film with a water absorption rate of no more than 8%, improving waterproof performance; composite flame retardants impart good fire safety.

[0059] The addition of sound-absorbing materials improves sound insulation and reduces noise transmission by about 30% to 40%, and graphene quantum dots and carbon nanotubes improve thermal insulation and reduce building energy consumption.

[0060] Redispersible latex powder improves flexibility and bonding properties, and enhances the wall's resistance to cracking and earthquakes.

[0061] The raw material pretreatment is optimized to remove impurities and moisture from the recycled aggregate, reduce water absorption, improve bonding performance with the cement matrix, and make the wall material structure more uniform and dense.

[0062] Advanced mixing technology is used to ensure uniform mixing of components and improve the consistency of material performance.

[0063] The forming and maintenance efficiency is improved, shortening the time by about 50% to 70%, meeting the needs of rapid construction.

[0064] Improve the quality inspection and traceability system to ensure stable and reliable product quality, and use intelligent packaging technology to facilitate storage, transportation and management. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 It is a process flow chart for preparing recycled concrete wall materials. DETAILED DESCRIPTION

[0066] A recycled concrete wall material comprising the following components by weight:

[0067] Recycled coarse aggregate: 300 to 500 parts, the particle size of recycled coarse aggregate is 5 mm to 30 mm, and its source is the product of construction waste after crushing, screening and washing, with a water absorption rate not exceeding 8% and a crushing index not exceeding 25%;

[0068] Recycled fine aggregate: 200 to 400 parts. The particle size of recycled fine aggregate is 0.15 mm to 4.75 mm. It is made from waste concrete and bricks and tiles in construction waste through a specific process, and the fineness modulus is between 2.3 and 3.0;

[0069] Cement: 150 to 300 parts, using ordinary Portland cement, with a strength grade of no less than 42.5, and its quality should comply with relevant national standards;

[0070] Fly ash: 30 to 80 parts. The fineness of the fly ash shall not exceed 20% after passing through a 45μm square mesh sieve, the loss on ignition shall not exceed 8%, and its activity index shall not be less than 70%;

[0071] Water reducing agent: 3 to 8 parts, use high-efficiency polycarboxylate water reducing agent, the water reducing rate should not be less than 25%;

[0072] Reinforcement fiber: 5 to 15 parts, the reinforcement fiber is a mixed fiber composed of polypropylene fiber and basalt fiber in a mass ratio of 1:2, and the fiber length is 6 mm to 12 mm;

[0073] Modified composition: 20 to 30 parts, the modified composition consists of nano silicon dioxide, silica fume, redispersible latex powder, graphene quantum dots and carbon nanotubes in a mass ratio of 3:4:2:0.5:0.5.

[0074] Example 1

[0075] S1, raw material pretreatment steps:

[0076] 500kg of recycled coarse aggregate and 400kg of recycled fine aggregate are cleaned and dried respectively to remove impurities and moisture. The cleaning process adopts a multi-stage flushing process to ensure that the attachments and dust on the surface of the aggregate are effectively removed. The moisture content of the dried aggregate does not exceed 2%. Surface modification treatment is then carried out, and the surface of the aggregate is sprayed or immersed with a silane coupling agent.

[0077] 300kg cement, 80kg fly ash and 12kg slag powder were sieved with a mesh size of 0.3mm to remove lumps and large particles of impurities to ensure the fineness and uniformity of the raw materials;

[0078] 15kg of reinforcing fibers were dispersed by combining mechanical stirring with adding dispersant to make the fibers evenly distributed in the material to avoid agglomeration. The amount of dispersant water glass was 0.15kg.

[0079] A modified composition consisting of 9 kg of nano-silicon dioxide, 12 kg of silica fume, 6 kg of redispersible latex powder, 1.5 kg of graphene quantum dots and 1.5 kg of carbon nanotubes was premixed to ensure that the components were evenly mixed to form a modified composition for use.

[0080] S2, mixing and stirring step:

[0081] Add 400kg of pretreated recycled coarse aggregate, 300kg of recycled fine aggregate, 250kg of cement, 60kg of fly ash, and 10kg of slag powder into a forced mixer, stir for 1 to 2 minutes, and add 0.1kg of sodium dodecylbenzene sulfonate to preliminarily mix the raw materials;

[0082] Then add 120kg water, 8kg water reducer, 45kg waterproofing agent and 80kg flame retardant, and continue stirring for 2 to 3 minutes to fully mix the materials;

[0083] During the mixing process, 15 kg of reinforcing fibers, 30 kg of modified composition and 100 kg of rock wool were added in stages to ensure that the fibers and modified composition were evenly dispersed in the concrete while avoiding damage to the fibers.

[0084] Ultrasonic assisted stirring technology is used to utilize the cavitation effect and mechanical effect of ultrasound to promote mixing and chemical reaction between components and improve the uniformity and performance of materials. The frequency of ultrasound is 30kHz and the power is 1000W.

[0085] S3, molding and curing steps:

[0086] Pour the stirred concrete mixture into the pre-prepared mold and use vibration molding to compact the material. The vibration frequency is 50Hz and the vibration time is 30 seconds to ensure that there are no pores and gaps inside the material.

[0087] The formed wall materials are subjected to vacuum dehydration technology, which places the formed wall materials in a vacuum environment. The discharge of water is accelerated by reducing the air pressure, thereby improving the density and early strength of the materials. The vacuum degree is controlled at -0.08MPa and the dehydration time is 20 minutes. Moisturizing maintenance is carried out at room temperature for 7 days. During the maintenance process, plastic film is used to maintain the humidity on the surface of the material, promote the hydration reaction of the cement and the development of the material strength.

[0088] S4, quality inspection steps:

[0089] The wall materials that have been cured are subjected to quality inspection, and the inspection items include compressive strength, tensile strength, water absorption rate, and thermal conductivity, to ensure that the performance of the materials meets the design requirements and relevant standards, among which the compressive strength is not less than 20MPa, the tensile strength is not less than 2MPa, and the water absorption rate does not exceed 8%.

[0090] Comparative Example 1: No modified composition was added, and the remaining processes were the same as in Example 1.

[0091] Comparative Example 2: No waterproofing agent was added, and the rest of the process was the same as in Example 1.

[0092] Performance test: Example 1 and Comparative Example 1 were tested according to GB / T 50081-2019.

[0093] Table 1

[0094] Group Compressive strength(MPa) Tensile strength(MPa) Water absorption (%) Example 1 23 2.2 7.5 Comparative Example 1 18 1.9 - Comparative Example 2 - - 12.5

[0095] As can be seen from Table 1, the compressive strength and tensile strength of Example 1 are higher than those of Comparative Example 1, the material with the modified composition added has higher strength, the water absorption of Example 1 is lower than that of Comparative Example 2, and the material with the waterproofing agent added has better waterproofness.

[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A recycled concrete wall material, characterized in that: Contains the following components by weight: Recycled coarse aggregate: 300 to 500 parts, the particle size of recycled coarse aggregate is 5 mm to 30 mm, and its source is the product of construction waste after crushing, screening and washing, with a water absorption rate not exceeding 8% and a crushing index not exceeding 25%; Recycled fine aggregate: 200 to 400 parts. The particle size of recycled fine aggregate is 0.15 mm to 4.75 mm. It is made from waste concrete and bricks and tiles in construction waste through a specific process, and the fineness modulus is between 2.3 and 3.0; Cement: 150 to 300 parts, using ordinary Portland cement, with a strength grade of no less than 42.5, and its quality should comply with relevant national standards; Fly ash: 30 to 80 parts. The fineness of the fly ash shall not exceed 20% after passing through a 45μm square mesh sieve, the loss on ignition shall not exceed 8%, and its activity index shall not be less than 70%; Water reducing agent: 3 to 8 parts, use high-efficiency polycarboxylate water reducing agent, the water reducing rate should not be less than 25%; Reinforcement fiber: 5 to 15 parts, the reinforcement fiber is a mixed fiber composed of polypropylene fiber and basalt fiber in a mass ratio of 1:2, and the fiber length is 6 mm to 12 mm; Modified composition: 20 to 30 parts, the modified composition consists of nano silicon dioxide, silica fume, redispersible latex powder, graphene quantum dots and carbon nanotubes in a mass ratio of 3:4:2:0.5:0.

5.

2. The recycled concrete wall material according to claim 1, characterized in that: The formula also contains 5 to 12 parts by weight of slag powder, the specific surface area of ​​which is not less than 400m 2 / kg, and its activity index is not less than 95%.

3. The recycled concrete wall material according to claim 1, characterized in that: The following steps are involved: S1, raw material pretreatment steps: The recycled coarse aggregate and recycled fine aggregate are cleaned and dried separately to remove impurities and moisture. The cleaning process adopts a multi-stage flushing process to ensure that the attachments and dust on the surface of the aggregate are effectively removed, and the moisture content of the dried aggregate does not exceed 2%; Cement, fly ash and slag powder are screened with a mesh size of 0.3 mm to remove lumps and large particles of impurities to ensure the fineness and uniformity of the raw materials; The reinforcing fibers are dispersed by combining mechanical stirring with the addition of dispersants to ensure that the fibers are evenly distributed in the material to avoid agglomeration. The amount of dispersants used is 1% to 2% of the fiber mass. Premixing a modified composition consisting of nano-silicon dioxide, silica fume, redispersible latex powder, graphene quantum dots and carbon nanotubes to ensure that the components are evenly mixed to form a modified composition for standby use; S2, mixing and stirring step: Add the pre-treated recycled coarse aggregate, recycled fine aggregate, cement, fly ash and slag powder into a forced mixer and stir for 1 to 2 minutes to preliminarily mix the raw materials; Then add water and water reducing agent, the amount of water is between 0.3 and 0.5 for the water-binder ratio, and continue stirring for 2 to 3 minutes to fully mix the materials; During the mixing process, reinforcing fibers and modified compositions are added in stages to ensure that the fibers and modified compositions can be evenly dispersed in the concrete while avoiding damage to the fibers; S3, molding and curing steps: Pour the stirred concrete mixture into a pre-prepared mold and use vibration molding or extrusion molding to compact the material. The vibration frequency is 30Hz to 50Hz and the vibration time is 10 seconds to 30 seconds to ensure that there are no pores and gaps inside the material. After forming, the wall material is kept moisturized at room temperature for no less than 7 days. During the curing process, plastic film is covered or curing agent is sprayed to maintain the humidity of the material surface, promote the hydration reaction of cement and the development of material strength. S4, quality inspection steps: The wall materials that have been cured are subjected to quality inspection, and the inspection items include compressive strength, tensile strength, water absorption rate, and thermal conductivity, to ensure that the performance of the materials meets the design requirements and relevant standards, among which the compressive strength is not less than 20MPa, the tensile strength is not less than 2MPa, and the water absorption rate does not exceed 8%.

4. The recycled concrete wall material according to claim 3, characterized in that: In the step S1, the recycled aggregate may be subjected to surface modification treatment, and the aggregate surface may be sprayed or soaked with a silane coupling agent or a polymer emulsion to improve the bonding performance between the aggregate and the cement matrix. The water absorption rate of the treated aggregate surface is reduced, and the bonding strength with the cement is improved; In the step S2, an air entraining agent or a defoaming agent is added as needed to adjust the air content and workability of the concrete, the amount of the air entraining agent is 0.01% to 0.05% of the mass of the cement, and the amount of the defoaming agent is 0.01% to 0.03% of the mass of the cement; In step S3, steam curing or hot water curing can be used to accelerate the curing method, shorten the curing time and improve production efficiency. The temperature of steam curing is 60°C to 90°C, and the curing time is 8 hours to 24 hours; the water temperature of hot water curing is 40°C to 60°C, and the curing time is not less than 48 hours.

5. A recycled concrete wall material according to any one of claims 1 to 4, characterized in that: Add a special waterproofing agent to the formula, which is a mixed waterproofing agent composed of a silicone waterproofing agent and a polymer cement-based waterproofing coating in a mass ratio of 1:2, and the added amount is 2% to 5% of the total mass of the material; According to the fire protection requirements of the wall, flame retardants can be added, using a composite flame retardant composed of aluminum hydroxide and magnesium hydroxide in a mass ratio of 1:1, and the added amount is 5% to 10% of the total mass of the material.

6. A recycled concrete wall material according to any one of claims 1 to 4, characterized in that: In step S2, an ultrasonic-assisted stirring technique may be used, wherein the frequency of the ultrasonic wave is 20 kHz to 40 kHz, the power is 500 W to 1000 W, and the stirring time is 5 minutes to 10 minutes; In step S3, vacuum dehydration technology can be used to place the formed wall material in a vacuum environment, accelerate the discharge of moisture by reducing the air pressure, and improve the density and early strength of the material. The vacuum degree is controlled at -0.06MPa to -0.08MPa, and the dehydration time is 10 minutes to 20 minutes.

7. A recycled concrete wall material according to any one of claims 1 to 4, characterized in that: The sound insulation performance of the wall material is optimized by adding sound-absorbing materials such as perlite and rock wool to the formula. The amount of sound-absorbing materials added is 10% to 20% of the total material mass.

Citation Information

Cited By

  • Full-recycled concrete as well as preparation method and application thereof

    CN119569399A

  • A fully recycled concrete and its preparation method and application

    CN119569399B

  • Ecological restoration matrix based on regenerated material and preparation method thereof

    CN120309302A

  • An ecological restoration substrate based on recycled material and a method for its production

    CN120309302B

  • Fabricated thermal insulation firewall based on recycled concrete

    CN120592375A